Pinjaman Online (Pinjol) Dalam Perspektif Hukum Ekonomi Islam dan Hukum Positif - Taufik, Azhar; Supyadillah, Asep; Amin, Muhammar; Prasetyo, Rifki Dwi (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2024)
This research focuses on Online Loans (Pinjol) from the perspective of Islamic Economic Law and Positive Law. This research was conducted to focus on two questions, namely (1) How are Online Loans (Pinjol) from the perspective of Islamic Economic Law? (2) What about Online Loans (Pinjol) in a Positive Legal Perspective? This research produced findings, (1) that Online Loans (Pinjol) are permitted in Islamic Economic Law by referring to the provisions contained in the Al Qur'an, Hadith, Ulama Opinions and MUI Fatwa Decisions. However, it is necessary to pay attention to several things, namely not conflicting with sharia principles and still paying attention to the principles of justice, balance, fairness in accordance with sharia and applicable laws. (2) Meanwhile, in positive law it is stated in the OJK regulations that Pinjol must submit to and obey the laws relating to the provisions of online/digital economic transactions by paying attention to the general provisions contained in the Criminal Code in force in Indonesia.